Personalized compression therapeutic textiles: digital design, development, and biomechanical evaluation - Shi, Yu; Liu, Rong; Ye, Chongyang (Frontiers in Bioengineering and Biotechnology, 2024)
Physical-based external compression medical modalities could provide sustainable interfacial pressure dosages for daily healthcare prophylaxis and clinic treatment of chronic venous disease (CVD). However, conventional ready-made of compression therapeutic materials (CTs) with improper morphologies and ill-fitting of pressure exertions frequently limit the patient compliance in practical application. Therefore, the present study fabricated the personalized CTs for various subjects through the proposed comprehensive manufacturing system. The individual geometric dimensions and morphologic profiles of lower extremities were characterized based on the threedimensional (3D) body scanning and reverse engineering technologies. Through body anthropometric analysis and pressure optimization, the knitting yarn and machinery variables were determined as the digital design strategies for 3D seamless fabrication of CTs. Then, to visually simulate the generated pressure mappings of developed CTs, the patient-specific 3D finite element (FE) CT-leg modellings with high accuracy and acceptability (pressure prediction precision: 11.00±7.78%) were established based on the constructed lower limb models and determined tissue stiffness. Moreover, through the actual in vivo trails, the prepared customized CTs efficiently (Sig. <0.05, ρ= 0.97) distributed the expected pressure requirements referred to the prescribed compression magnitudes (pressure discrepancy ratio: 10.08±7.75%). Furtherly, the movement abilities and comfortable perceptions were evaluated subjectively for the ergonomic wearing comforts (EWCs) assessments. Thus, this study promotes the precise pressure management and clinical efficacy for targeted users and leads an operable development approach for related medical biomaterials in compression therapy.